2012
DOI: 10.1007/s12471-012-0276-8
|View full text |Cite
|
Sign up to set email alerts
|

Critical hand ischaemia after transradial cardiac catheterisation: an uncommon complication of a common procedure

Abstract: We describe a case of critical hand ischaemia after transradial cardiac catheterisation. The patient presented with hand ischaemia 5 days after transradial coronary angiography. Urgent angiography demonstrated radial artery occlusion with embolisation to the palmar arch and digital arteries. The ischaemia was refractory to an extensive thrombolytic regimen, and subsequently, the patient was referred to the vascular surgeon for urgent thrombectomy and patch angioplasty. The patient recovered slowly and no amput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…Therefore, symptomatic RAO is relatively rare and hand ischemia is exceedingly rare [3]. Up to date, there have been only 5 reported cases of symptomatic RAO with hand ischemia (Table 1) [4][5][6][7][8]. Most of these patients presented within one month from the index procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, symptomatic RAO is relatively rare and hand ischemia is exceedingly rare [3]. Up to date, there have been only 5 reported cases of symptomatic RAO with hand ischemia (Table 1) [4][5][6][7][8]. Most of these patients presented within one month from the index procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This does not guarantee that distal finger ischemia or gangrene cannot occur after radial artery manipulation. However, in most cases of distal ischemia reported in the published data, AT results were considered normal before the procedure, and angiographic findings revealed distal embolization in addition to RAO (7).…”
Section: See Page 1833mentioning
confidence: 90%
“…Currently two cases of hand ischemia after cardiac catheterization are documented in the literature, both solved without resorting to amputation. 68,69 Thus, an Allen test should be always performed before TRA procedure to test ulnar supply to the palmar arch before radial cannulation, even if data in the literature are conflicting: some authors reported ischemic complications despite a brisk Allen test, whereas others showed how an abnormal Allen test was not predictive of ischemic complications. 70 A modified Allen test using plethysmography (Barbeau's test) has been shown to be more effective than traditional Allen test.…”
Section: Access-site Thrombotic Complicationsmentioning
confidence: 99%